2020
DOI: 10.1108/heswbl-03-2019-0041
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong learning mindset and career success: evidence from the field of accounting and finance

Abstract: PurposeThe purpose of this article is to examine the relationship between a lifelong learning mindset and career success. A lifelong learning mindset is a way of approaching one's work with curiosity, strategic thinking, and resilience. Career success refers to objective (e.g., number of promotions) and subjective (e.g., job satisfaction) indicators of progress and fulfillment in one's work.Design/methodology/approachTwo studies are presented. Both studies draw from an accounting and finance program at a Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 42 publications
3
42
0
3
Order By: Relevance
“…The fifth research area is cluster 5 (purple), made up of 11 nodes called 'Job Satisfaction'. In this cluster, in Drewery's research, objective and subjective indicators are attributed to professional success; within the subjective ones, job satisfaction is included [145]. Likewise, wellbeing, life goals, and values must be considered to achieve job satisfaction [146].…”
Section: Co-occurrence Network Of Author Abstractmentioning
confidence: 99%
“…The fifth research area is cluster 5 (purple), made up of 11 nodes called 'Job Satisfaction'. In this cluster, in Drewery's research, objective and subjective indicators are attributed to professional success; within the subjective ones, job satisfaction is included [145]. Likewise, wellbeing, life goals, and values must be considered to achieve job satisfaction [146].…”
Section: Co-occurrence Network Of Author Abstractmentioning
confidence: 99%
“…This may prevent additional challenges in the workplace due to lower self-perceptions of leadership. Some research has found that student programs that expose students to future challenges in the workplace help young people build the resilience that they will need when employed (Drewery et al, 2020).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Memang pada kenyataannya perspektif belajar dalam aktivitas orang dewasa, tidak mudah ditemui. Padahal adanya pola pikir belajar dari seseorang menjadi salah satu faktor utama dalam perjalanan kesuksesan karir mereka (Drewery et al, 2020).…”
Section: Hasil Dan Diskusi 1 Belajar Sepanjang Hayatunclassified
“…Penelitian di masa depan memerlukan waktu yang tidak sedikit untuk mengkaji berbagai perspektif dan konseptual yang berhubungan dengan inovasi yang dipandang dalam kacamata belajar sepanjang hayat. seseorang dapat menciptakan ide baru atau inovasi dalam kehidupannya, maka berkorelasi dengan kesuksesan karir pribadinya (Drewery et al, 2020). Di sisi kelompok usaha pun, apabila perusahaan dapat berinovasi, maka mereka dapat mempertahankan dan mendorong kesuksesan perusahaannya (Kamal, 2006).…”
unclassified
See 1 more Smart Citation